Does the Choice of Cooking Fuel Impact Happiness and Life Satisfaction? - Tatik Sumiyati; Djoni Hartono (Jurnal Ekonomi Pembangunan)
The subjective experiences and perceptions of people when switching to cleaner cooking fuels are typically ignored in favor of objective indicators like respiratory health or time spent gathering firewood. Given that a sizable section of the populace still cooks using traditional biomass fuels while the country moves toward cleaner fuels like LPG and electricity, this research gap is particularly important in Indonesia. This study examines the association between the use of cleaner cooking fuels and two dimensions of subjective well-being: happiness and life satisfaction, using data from the most recent wave of the Indonesia Family Life Survey (IFLS). Propensity Score Matching (PSM) and Ordinary Least Squares (OLS) are used in this analysis to mitigate selection bias and precisely evaluate treatment effects. The empirical results reveal that the use of clean cooking fuel positively impacts an individual's subjective well-being, enhancing both happiness and life satisfaction. Individuals in rural areas get a more pronounced effect. The findings will offer important perspectives for decision-makers and interested parties focused on enhancing access to clean cooking energy and elevating subjective well-being in Indonesia, particularly in rural regions.